Significance of demographic variables for targeting of internet advertisements - Stříteský, Václav; Stříteský, Marek; Quigley, Martin John David; Říha, David (Business, Management and Economics Engineering, 2016)
Broad ad targeting options belong among the major advantages of internet advertising. Demographic targeting has become a standard option in most of on-line advertising systems. There are more ways how to target on-line advertisements by using demographic variables. In some cases, e.g., social media, we can use data from user registrations. Modern technologies enable to estimate the demographic profile of internet users using on behavioural data. The traditional approach to the demographic targeting of advertisements based on affinity targeting assumes the existence of internet servers with sufficient homogeneity of visits. The aim of this article is to identify the differences in the internet content consumption habits of Czech internet users based on gender and age. The analysis is based on the data from the extensive research which was carried out by the Netmonitor project, and which was provided for the purposes of this study by the Association for Internet Development (SPIR). The research results show that the traditional affinity-based method of targeting according to gender and age is still suitable on the Czech internet. On the other hand, in some cases, the traditional approach of ad targeting based on affinity leads to wasted ad impressions that miss defined target group.